Multidimensional sleep quality of dependent self-employment workers - Lee, Sang Ha (Ann Occup Environ Med, 2020)
BACKGROUND: The number of workers in non-standard employment (NSE) is increasing due to industrial change and technological development. Dependent self-employment (DSE), a type of NSE, was created decades ago. Despite the problems associated with this new type of employment, few studies have been conducted on the effects by DSE on health, especially sleep quality. This study aims to determine the relationship between DSE and sleep quality. METHODS: This study analyzed data of 50,250 wage workers from the fifth Korean Working Conditions Survey. Workers that did not respond or refused to answer any questions related to variables were excluded, and finally 36,709 participants were included in this study. A total of 2,287 workers (6.2%) were compared with non-DSE (34,422; 93.8%) workers, and multiple logistic regression analyses were applied. RESULTS: DSE status had a significant association with difficulty falling asleep (odds ratio [OR]: 1.331, 95% confidence interval [CI]: 1.178–1.504), difficulty maintaining sleep (OR: 1.279; 95% CI: 1.125–1.455), and extreme fatigue after waking up (OR: 1.331; 95% CI: 1.184–1.496). A multiple logistic regression of the variables for sleep quality in DSE showed a significant association with exposure to physical factors for all types of poor sleep quality as well as shift work for difficulty maintaining sleep with extreme fatigue after waking up. Long working hours and emotional labor were also associated with extreme fatigue after waking up. CONCLUSIONS: This study shows a significant association between DSE and poor sleep quality, especially when workers were exposed to physical risk factors (noise, vibration, abnormal temperature, etc.) and shift work.